Integrated nutrient and performance of okra (Abelmoschus esculentus (L.) Moench) under Morus based agroforestry system in mid-hills of Himachal Pradesh - Bhuyan, Bandan Kumar; Thakur, C.L.; Sharma, Harish; Kumar, Dhirender (Indian Journal of Agroforestry, 2021)
The present investigation was carried out under Morus based agri-silviculture system, to study the effect of application of integrated nutrient on growth and yield of okra (Abelmoschus esculentus (L.) Moench). Organic manures (vermicompost, goat manure and poultry manure) were used in different combinations with Recommended Dose of Fertilizer (RDF) i.e. 100% organic manure, 75% organic manure, 50% organic manure and 100% RDF, to assess the performance of okra under four-year old Morus plantation planted during July, 2012. The results revealed that most of the growth and yield parameters were significantly influenced by the combinations of inorganic and organic nutrient inputs. Among different treatment combinations, T10 (100% poultry manure @25.08 q ha-1 along with basal dose of FYM @ 10 t ha-1) gave best results in terms of growth and yield of okra. Okra performed better when grown in open (without Morus tree) as compared to that grown as intercrop between rows of Morus. Further, with increased distance of crop from tree proximity, beneficial results in growth and yield of the crop were obtained.